Family boundaries : the invention of normality & dangerousness - Knowles, Caroline, 1954- (Broadview Press, 1996)
Family Boundaries shows what can be accomplished when families are viewed from the multi - perspectives of biography and of agencies charged with detecting and managing child abuse and setting boundaries of acceptable behavior in family life. Apart from our personal notions of the family, a social sense of it has developed from the professional practice - narratives which focus on dangerousness, thus rendering the family in rather rigid and archaic administrative terms. Furthermore, these administrative inventions of the family and the resulting attempts to effect child protection take on powerful meanings because they are supported in social policy and in law, and are constantly reflected in popular media images of family. The regulatory apparatus of these administrative inventions of family, the author argues, falls disproportionately on the poor and on mothers to whom it assigns a pivotal role as internal regulators. This book surveys the conceptions of motherhood, fatherhood, and childhood that emerge from the practices of agencies. It urges that there is a need to create forms of family management which balance the necessity to protect children with the rights of mothers and the responsibilities of fathers. In doing so, Family Boundaries presents fresh insight into how we think about family relationships and the demands they impose.